Missense Mutations of Human Hsp60: A Computational Analysis to Unveil Their Pathological Significance - Vitale, Alessandra Maria; Conway de Macario, Everly; Alessandro, Riccardo; Cappello, Francesco; Macario, Alberto J. L.; Marino Gammazza, Antonella (Frontiers in Genetics, 2020)
Two chaperonopathies have been linked to mutations in the human hsp60 (hHsp60; HSPD1) gene, but other existing variants might cause diseases, even if there is no comprehensive information about this possibility. To fill this vacuum, which might be at the basis of misdiagnoses or simply ignorance of chaperonopathies in patients who would benefit by proper identification of their ailments, we searched the sequenced human genomes available in public databases to determine the range of missense mutations in the single hsp60 gene. A total of 224 missense mutations were identified, including those already characterized. Detailed examination of these mutations was carried out to assess their possible impact on protein structure-function, considering: (a) the properties of individual amino acids; (b) the known functions of the amino acids in the human Hsp60 and/or in the highly similar bacterial ortholog GroEL; (c) the location of the mutant amino acids in the monomers and oligomers; and (d) structure-function relationships inferred from crystal structures. And we also applyed a bioinformatics tool for predicting impact of mutations on proteins. A portion of these genetic variants could have a deleterious impact on protein structure-function, , but have not yet been associated with any pathology. Are these variants causing disease with mild clinical manifestations and are, therefore, being overlooked? Or are they causing overt disease, which is misdiagnosed? Our data indicate that more chaperonopathies might occur than is currently acknowledged, and that awareness of chaperonopathies among medical personnel will increase their detection and improve patient management.